Goniotomy with a single‐use dual blade: Short‐term results. Issue 9 (September 2017) - Greenwood, Michael D.; Seibold, Leonard K.; Radcliffe, Nathan M.; Dorairaj, Syril K.; Aref, Ahmad A.; Román, Jesús Jimenez; Lazcano‐Gomez, Gabriel S.; Darlington, Jason K.; Abdullah, Suhail; Jasek, Mark C.; Bahjri, Khaled A.; Berdahl, John P.
Abstract : Purpose : To evaluate the intraocular pressure (IOP)–lowering efficacy and safety of a single‐use dual blade (Kahook) in patients with mild to end‐stage glaucoma. Setting : International multicenter ophthalmic care centers. Design : Prospective interventional case series. Methods : Consecutive patients with glaucoma who had phacoemulsification plus goniotomy with the single‐use dual blade were enrolled in this study. Each center collected deidentified clinical data, including preoperative and postoperative IOP, medication use, adverse events, and whether additional surgery was required during a 6‐month follow‐up. Results : Of the 71 eyes included in this study, 70% had primary open‐angle glaucoma. Other diagnoses included angle‐closure, pigmentary, pseudoexfoliative, and normal‐tension glaucoma. Sixty‐five percent of eyes were classified as having mild to moderate glaucoma and 35%, severe glaucoma. The mean baseline IOP decreased from 17.4 mm Hg ± 5.2 (SD) to 12.8 ± 2.6 mm Hg 6 months postoperatively and the hypotensive medication use decreased from 1.6 ± 1.3 to 0.9 ± 1.0, respectively ( P < .001 and P = .005, respectively). The most common observation was blood reflux during surgery (39.4%). Conclusion : Single‐use dual blade goniotomy plus phacoemulsification resulted in a significant and sustained reduction in IOP and a decrease in glaucoma medications after 6 months of follow‐up.